Chemical physical characterization of rapadura added with clay almond marketed in the region of Rio Verde, Goiás State, Brazil (Research, Society and Development, 2020)
Rapadura is made from sugarcane juice highly concentrated and solidified in blocks, varying in shape and weight. It is a nutritious product and source of carbohydrates such as sucrose, fructose and glucose, in addition to minerals and vitamins. Baru almonds have a higher content of unsaturated fatty acids and a lower content of saturated fatty acids than peanuts and Brazil nuts. Although nutritious and with great technological potential, there are few studies related to the evaluation of products obtained from baru almonds. The present study aimed to evaluate the physical and chemical characteristics of the barley almond rapadura added in the region of Rio Verde - Goiás. It was determined, humidity, water activity, pH, total acidity, lipids, proteins, ash, carbohydrates and total sugar from rapadura following the methodologies described by Institute Adolfo Lutz and reducing sugars by the DNS method. It was obtained from the present study, the physical and chemical characteristics of the rapadura added with baru almond, the results of the analyzes indicated an increase in the levels of lipids, proteins and minerals in comparison to the values ​​presented by the traditional rapadura.